Small vessel disease and clinical outcomes after IV rt‐PA treatment. (23rd February 2017) - Arba, F.; Inzitari, D.; Ali, M.; Warach, S. J.; Luby, M.; Lees, K. R.; ,
Abstract : Introduction: Cerebral small vessel disease (SVD) contributes to dementia and disability in the elderly, and may negatively affect stroke outcomes. We aimed to evaluate to what extent single features and global burden of SVD detected with magnetic resonance (MR) are associated with worse outcomes in patients with ischaemic stroke treated with intravenous thrombolysis. Methods: We accessed anonymized data and MR images from the Stroke Imaging Repository (STIR) and the Virtual International Stroke Trials Archive (VISTA) Imaging. We described SVD features using validated scales and quantified the global burden of SVD with a combined score. Our mainoutcome was the modified Rankin Scale (mRS) at 90 days after stroke. We used logistic regression and ordinal regression models (adjusted for age, sex, stroke severity, onset to treatment time) to examine the associations between each SVD feature, SVD global burden and clinical outcomes. Results: A total of 259 patients had MR scans available at baseline (mean age±SD=68.7±15.5 years; 131 [49%] males). After adjustment for confounders, severe white matter changes were associated with disability (OR=5.14; 95%CI=2.30‐11.48), functional dependency (OR=4.38; 95%CI=2.10‐9.13) and worse outcomes in ordinal analysis (OR=2.71; 95%CI=1.25‐5.85). SVD score was associated with disability (OR=1.66; 95%CI=1.03‐2.66) and functional dependency (OR=1.47; 95%CI=1.00‐2.45). Lacunes, enlarged perivascular spaces and brain atrophy showed no association with clinical outcomes. Conclusion: Our results suggest that SVD negatively affects stroke outcomes after intravenous thrombolysis. Although white matter changes seem to be the major driver in relation to worse outcomes, global estimation of SVD is feasible and may provide helpful information.